Beyond the Dual Paraneoplastic Syndromes of Small-Cell Lung Cancer with ADH and ACTH Secretion: A Case Report with Literature Review and Future Implications - Krishna Adit Agarwal; Myat Han Soe (Case Reports in Oncological Medicine, 2018)
We present a case of small-cell lung cancer (SCLC) with syndrome of inappropriate antidiuretic hormone secretion (SIADH) in which serum sodium gradually normalized with the onset of hypertension, refractory hypokalemia, and chloride-resistant metabolic alkalosis due to ectopic adrenocorticotrophic hormone (ACTH) secretion (EAS). In this case report, we discuss the diagnostic challenges of dual paraneoplastic syndromes with SIADH and EAS, management of SCLC with paraneoplastic endocrinopathies, and their prognostic impact on SCLC. In addition, we discuss neuroendocrine differentiation and ectopic hormone production in relation to intratumoral heterogeneity in SCLC and propose tumor microenvironment and hormonal and metabolic dependence as important determinants of tumor growth and survival.